SMASHing the low surface brightness SMC. Issue 1 (18th August 2020) - Massana, Pol; Noël, Noelia E D; Nidever, David L; Erkal, Denis; de Boer, Thomas J L; Choi, Yumi; Majewski, Steven R; Olsen, Knut; Monachesi, Antonela; Gallart, Carme; Marel, Roeland P van der; Ruiz-Lara, Tomás; et al.
ABSTRACT: The periphery of the Small Magellanic Cloud (SMC) can unlock important information regarding galaxy formation and evolution in interacting systems. Here, we present a detailed study of the extended stellar structure of the SMC using deep colour–magnitude diagrams, obtained as part of the Survey of the MAgellanic Stellar History (SMASH). Special care was taken in the decontamination of our data from Milky Way (MW) foreground stars, including from foreground globular clusters NGC 362 and 47 Tuc. We derived the SMC surface brightness using a 'conservative' approach from which we calculated the general parameters of the SMC, finding a staggered surface brightness profile. We also traced the fainter outskirts by constructing a stellar density profile. This approach, based on stellar counts of the oldest main-sequence turn-off stars, uncovered a tidally disrupted stellar feature that reaches as far out as 12 deg from the SMC centre. We also serendipitously found a faint feature of unknown origin located at ∼14 deg from the centre of the SMC and that we tentatively associated with a more distant structure. We compared our results to in-house simulations of a 1 × 10 9 M⊙ SMC, finding that its elliptical shape can be explained by its tidal disruption under the combined presence of the MW and the Large Magellanic Cloud. Finally, we found that the older stellar populations show a smooth profile while the younger component presents a jump in the density followed by a flat profile, confirming the heavily disturbed nature of the SMC.